Investigation of zircon by CL (Cathodoluminescence) and Raman Spectroscopy - Kilic, Ayse Didem (Iop Publishing Ltd, 2016)
Puturge metamorphites consists of schist, gneisse, metagranite gneisse, amphibolite, kyanite quartzite and marble type rocks. Mineralogical studies, geochemical analysis (LA-ICPMS), Raman spectroscopy and cathodoluminescence (CL) imaging that it representing amphibolite facies and greenschiste facies. Zircon imaging called as a metamict from the cathodoluminescence images of zircon minerals. The partially radiated zircon particles is higher radiogenetic mineral ratio in comparison with other zircon particles. The ratio of the radiogenetic elements (U, Pb and Th) arises from chemical difference between the core and rims of zircons. The solubility of zircon effects environmental conditions such as high pH, Zr with hydroxyl ions. Especially alkaline fluids in environment can dissolve zircon. The results show that radiogenetic elements loss in zircons can be generated from metamict zircon through volume diffusion at low temperatures or by an external fluid (H2O). The loss of lead in zircon signifies that the fluids inserting the crystal lattice causes radiation damage processes.
World Multidisciplinary Earth Sciences symposium (WMESS) -- SEP 05-09, 2016 -- Prague, CZECH REPUBLIC
Keywords: Radiation-Damage